Enforced disappearance as crime against humanity in Rome Statute - Ševo Olivera (Crimen (Beograd), 2019)
The paper deals with enforced disappearance as a crime against humanity in the Rome Statute, as a source of law which precisely defines enforced disappearance for the first time. The author analyzes some particularities concerning the actus reus of this crime which contains two acts or two "stages", subjective element which is twofold, participation of the state or a political organization in the crime as a very important element of this crime, but also crime against humanity's common elements which need to be met for existence of this crime. The paper also contains analyze of the International Criminal Court's temporal jurisdiction because of its specificity concerning this crime. The author is giving a review of this crime elements and trying to point out eventual problems in further practice as well as potentially very extensive interpretation which can be found in literature.